Sarcolemmopathy: Muscular Dystrophies with Cell Membrane Defects - Ozawa, Eijiro (Brain Pathol, 2006)
In this article, we review the molecular pathology of muscular dystrophies caused by defects of proteins located within or near cell membranes. These disorders include Bethlem myopathy, merosinopathy, dystrophinopathy, sarcoglycanopathies, integrinopathy, dysferlinopathy and caveolinopathy. We refer to these diseases collectively as sarcolemmopathy. Here, we describe the biological functions of these proteins in the context of muscular contractions and their roles in the infrastructure of muscle; defects of muscle infrastructures cause those diseases. As an example, in dystrophinopathy, cell membranes have mechanical defects due to the absence of dystrophin. Cracks of the cell membrane induced by muscle contraction may allow the influx and efflux of substances that trigger muscle cell degeneration. However, such cracks may be resealed on relaxation. In addition, dystrophinopathy causes secondary defects of various dystrophin‐associated proteins suggesting that defects in cell signaling participate in the pathologic process. With regard to other sarcolemmopathies, we discuss pathological mechanisms based on available data.